Optimisation of CoMP-based cellular network design and its radio network parameters for next generation HetNet using Taguchi's method. (30th April 2020) - Dastoor, Sarosh K.; Dalal, Upena; Sarvaiya, Jignesh
A heterogeneous network (HetNet) is a complex network made of variable cellular dimensions with different network topology. An erratic network design is valueless, unproductive and expensive. Research paper describes coordination of multipoint transmission, in which a collection of transmitting Base Stations (BS) dynamically harmonises their transmission among themselves, enhancing the coverage to the edge users. The proposed cellular planning strategy uses variable radii cells forming a cluster in a given region to be dimensioned. For a given cluster, minimum distance ( d min ) between two cells has been calculated and using proposed (1/3 d min ) dimensioning technique, the coverage radius of cells in a cluster is made, forming a HetNet. By optimising the network; coverage, cost and energy requirements could be minimised and optimisation of network performance parameters like transmission power, tilt and azimuth angle of antenna with the radius of cell provides cost-efficient deployment of a network. The research paper proposes the mathematical dimensioning model for the design of a HetNet as well as its performance parameters using Taguchi's method – a soft computing approach. The proposed approach has been compared with the conventional constant radius approach for dimensioning a network. The total power required to transmit has been drastically reduced by 22.7% as compared to constant radius cellular planning strategy. In addition, throughput of the proposed method was found to be 41.5% higher than the constant radius approach.